1999
DOI: 10.3171/foc.1999.7.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Microendoscopic posterior cervical foraminotomy: a cadaveric model and clinical application for cervical radiculopathy

Abstract: Cervical radiculopathy that is caused by either soft herniated disc material or foraminal stenosis is a common problem. Anterior and posterior surgical approaches are commonly performed to decompress the nerve root. The authors describe an endoscopic posterior foraminotomy procedure in which they use a rigid endoscope, in both a cadaveric model and in three clinical cases, including a multiple level case. Postoperatively, all patients returned to functional work status within 4 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…38 Several minimally invasive approaches have been developed including microscope-assisted "keyhole" foraminotomy, micro-endoscope, and endoscope-assisted techniques. [39][40][41][42] Ruetten and colleagues 43 were the first to describe "fullendoscopic" cervical approaches introducing the endoscope via a small tubular retractor. Kim and colleagues 44 reported similar clinical results comparing posterior tubular-based microscopeassisted with percutaneous endoscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…38 Several minimally invasive approaches have been developed including microscope-assisted "keyhole" foraminotomy, micro-endoscope, and endoscope-assisted techniques. [39][40][41][42] Ruetten and colleagues 43 were the first to describe "fullendoscopic" cervical approaches introducing the endoscope via a small tubular retractor. Kim and colleagues 44 reported similar clinical results comparing posterior tubular-based microscopeassisted with percutaneous endoscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term follow-up studies showed the fusion-related complications such as degeneration of adjacent segments, graft subsidence, implant failures, pseudarthrosis, rejection reaction, or access-related complications [6][7][8][9][10] . In order to avoid these complications caused by intervertebral fusion, various modi cations were reported to minimize surgical disturbance to the biomechanics of cervical spine [11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the 20th century, numerous specialists and researchers are committed to providing new insights into ESS, and a large number of articles about ESS are published annually to showed clinical application, cases report, the surgical technical note, safety and effectiveness. [19][20][21][22][23][24][25] Very recently, a bibliometric study on full-ESS demonstrated that the number of published articles increased by 41 times between 1997 and 2017. 26 However, the newest study focused only on full-ESS and could not fully reflect the field of ESS due to their exclusion of thoracoscopic spine surgery, and laparoscopic spine surgery, and nasoendoscopic spine surgery.…”
Section: Introductionmentioning
confidence: 99%